The Association of Weight Status with Physical Fitness among Chinese Children - Shang, Xianwen (Hindawi Publishing poration, 2010)
Objective. To investigate the association of weight status with physical fitness among Chinese children. Methods. A total of 6929 children aged 6–12 years were selected from 15 primary schools of 5 provincial capital cities in eastern China. The height and fasting body weight were measured. The age-, sex-specific BMI WHO criteria was used to define underweight, overweight and obesity. Physical fitness parameters including standing broad jump, 50 m sprint, and 50 m(∗)8 shuttle run were tested. Results. The prevalence of underweight, overweight, and obesity was 3.1%, 14.9%, and 7.8%, respectively. Boys performed better than girls, and the older children performed better than their younger counterparts for all physical fitness tests. No significant difference in all three physical fitness tests were found between children with underweight and with normal weight, and they both performed better than their counterparts with overweight and obese in all three physical fitness tests. The likelihood of achieving good performance was much lower among overweight and obese children in comparison with their counterparts with normal weight (OR = 0.13–0.54). Conclusions. An inverse association of obesity with cardiorespiratory fitness, muscle explosive strength, and speed was identified among Chinese children.